К вопросу о расчетно-экспериментальном определении параметров численных моделей корпусов транспортных средств - Пелешко, Евгений Витальевич; Васильев, Антон Юрьевич; Гриценко, Геннадий Дмитриевич; Бруль, С. Т.; Пономарев, Е. П. (НТУ "ХПИ", 2007)
The results of computational and experimental researches of models of hulls of the armoured troop-carrier BTR-80 and tractor MT-LB are presented. The rational parameters of finite-elements models of hulls of transport vehicles of the special setting for research of their stressed-deformed state are determined
Keywords: оценки погрешности; моделирование НДС; бронетранспортеры; многоцелевой тягач; легкобронированные машины; тактико-технические характеристики